1994
DOI: 10.1111/j.1559-1816.1994.tb02369.x
|View full text |Cite
|
Sign up to set email alerts
|

Work Values Among Professional Employees in Union and Nonunion Research Library Institutions

Abstract: This study explored the relationship between unions and professional librarians' w]ork values. Despite previous research findings on blue‐collar workers, this investigation found no significant differences in the work values of professionals in unionized versus nonunionized libraries. However, differences in work‐related values were traced when the present research looked just at the union group of the study. Data analysis indicated that registered union members and those most committed to their union placed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Synder, Verderber, and Morris (1986) noted that the research has usually compared samples from work sites with no union representation with those in which union membership is mandatory (Hovekamp, 1994). Nevertheless, these studies neither allow comparisons between union members and non-members, nor allow any implication on work settings in which unionization has hitherto not taken place.…”
Section: Unionsmentioning
confidence: 98%
“…Synder, Verderber, and Morris (1986) noted that the research has usually compared samples from work sites with no union representation with those in which union membership is mandatory (Hovekamp, 1994). Nevertheless, these studies neither allow comparisons between union members and non-members, nor allow any implication on work settings in which unionization has hitherto not taken place.…”
Section: Unionsmentioning
confidence: 98%
“…They also found similarities in the values held by library science students and faculty. Hovekamp (1994) studied the work values of unionised and non-unionised librarians in Association of Research Libraries (ARL) libraries and found no significant differences in the work values of librarians in unionised versus non-unionised libraries. Allen (1998) investigated the work values of library science students as compared to those of business students and found differences in their attitudes toward work.…”
Section: Electronic Accessmentioning
confidence: 99%
“…This literature helps inform an understanding of the possible effect of union affiliation on employees' perceptions of the work environment. Hovekamp (1994), for example, found no significant differences in the work values of union and nonunion professional librarians. However, in a survey of several major industrial sectors, Sanchez and Juetten (1988) found differences between union and nonunion members regarding satisfaction with salary issues.…”
Section: The Effects Of Union Membership On the Work Environmentmentioning
confidence: 95%
“…A second body of research has been conducted on union membership in business and industry, and has addressed a variety of topics including the impact of union status on job satisfaction (Berger, Olson, and Boudreau, 1983;Gordon and DeNisi, 1995), work attitudes (Boothe and Lincoln, 1993), level of commitment to employer (Conlon and Gallagher, 1987), and level of attachment to union and productivity (Meador and Walters, 1994). In addition, research that compares union and nonunion employees has investigated attitudes toward union representation (Hills, 1985), work values among professional employees (Hovekamp, 1994), the perceived role of unions (Keegan, 1987), and support for worker participation (Olson and Fenwick, 1986), among others. This literature helps inform an understanding of the possible effect of union affiliation on employees' perceptions of the work environment.…”
Section: The Effects Of Union Membership On the Work Environmentmentioning
confidence: 99%